2015
DOI: 10.3109/13561820.2015.1025373
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to test the effectiveness of an innovative interprofessional education assessment strategy

Abstract: The goals of this quasi-experimental pilot study were to test an assessment tool designed to evaluate students' teamwork skills, and to assess the effectiveness of an interprofessional education (IPE) course. Participants were health professional students (physical therapy, pharmacy, dental and osteopathic medicine), 24 of whom were second-year students who had previously taken part in an IPE course (experimental group), and 22 of whom were third years that had not (control group). Students interacted with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
(22 reference statements)
2
6
0
Order By: Relevance
“…Our finding that students who reported prior IPE experience scored higher compared to students reporting none, confirms observations from another study [37] and provides support for the efficacy of IPE for improving team behaviors. We speculate that the abbreviated scale is sensitive to performance differences between groups and can potentially function to evaluate the impact of new IPE curricula.…”
Section: Discussionsupporting
confidence: 90%
“…Our finding that students who reported prior IPE experience scored higher compared to students reporting none, confirms observations from another study [37] and provides support for the efficacy of IPE for improving team behaviors. We speculate that the abbreviated scale is sensitive to performance differences between groups and can potentially function to evaluate the impact of new IPE curricula.…”
Section: Discussionsupporting
confidence: 90%
“…Only 6.12% of these projects involved randomized experiments, a rate that is only slightly higher than a typical dissertation or thesis in the field of education. [4] These results support the notion that research in medical education has far more in common with [5] E D EdD Education Gucev [6] E D EdD Education Miller Juve [7] E D EdD Education Best [8] Q D PhD Engineering Hess [9] Q D DPH Public health McCoy [10] E D EdD Education Buck [11] Q D PhD Psychology Cheung [12] E T MS Medicine Wee [13] E D PhD Medicine Latham [14] E D EdD Education Carney [15] Q T MS Medicine Ford [16] Q D EdD Education Varthis [17] E D PhD Education Hill [18] E T MS Medicine E: Experimental design, Q: Quasi-experimental design, D: Dissertation, T: Thesis, DPH: Doctorate of public health the methodological conventions of education and the social and behavioral sciences than those of the medical and health sciences.…”
Section: Discussionsupporting
confidence: 71%
“…15 Although no standard assessment context exists for collaborative decision-making, Objective Structured Clinical Examination (OSCE) have been validated as a method to evaluate behavioural competencies, 18 and have been utilized in the pre-licensure setting to evaluate healthcare students' competency in interprofessional collaboration. [19][20][21][22] Emmert & Cai 19 and Zaudke et al 22 utilized team-based OSCE formats wherein students of different health disciplines interacted with a standardized patient asynchronously and synchronously, respectively. Although these studies demonstrate the utility of team-based OSCE in evaluating students' behavioural competency in interprofessional teamwork and communication, use of this OSCE design may be limited by logistical barriers, such as aligning schedules of students and assessors from different healthcare disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Domac et al 25 and Bzowyckyj et al 26 describe reflective journaling as a favourable method to assess students' reported experiences related to IPE and intercollaborative practice; however, it is more so a measure of attitude or affective learning, not of behavioural competence. 13,15 OSCE-based evaluations, as utilized to assess interprofessional collaborative practices of students from one 20 or more than one 19,22 healthcare profession, measure behavioural outcomes 13,15 and "transfer of knowledge, skills and/or attitudes." 13 Whether or not affective learning and attitudinal changes translate into long-term changes in associated behaviours has not been well-described in the literature.…”
mentioning
confidence: 99%